“FREQUENCY AND OUTCOME OF DYSLIPIDEMIA IN DIABETIC FOOT PATIENTS” - Muhammad Adnan Sarwar; Muhammad Moiez; Hamza Nasir; Anas Mustafa; Muhammad Saqib; Qudsia Babar (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Diabetic foot is a serious complication of diabetes mellitus, contributing to significant morbidity, mortality, and healthcare burden worldwide. Dyslipidemia is frequently observed in diabetic patients and has been implicated in vascular dysfunction and poor ulcer healing. However, limited data exist on its prevalence and impact in diabetic foot patients in Pakistan. Objective: To identify the prevalence of dyslipidemia and its clinical outcomes among patients with diabetic foot who present to Department of Medicine, Aziz Fatima Hospital, Faisalabad, Pakistan. Methods: This cross-sectional descriptive study was performed between October, 2024 and April, 2025 at the Department of Medicine, Aziz Fatima Hospital, Faisalabad, Pakistan. One hundred and eighty patients who had diabetic foot ulcers and type 2 diabetes were enrolled. Clinical assessment, ulcer grading, and fasting lipid profiles were conducted. Measures of outcomes evaluated were ulcer healing, surgical intervention, amputation, and in-hospital mortality. Results: Out of 180 patients, 108 (60%) were male and 72 (40%) were female, with a mean age of 56.8 years ± 9.4 years. There was dyslipidemia in 124 patients (68.9%). Abnormalities that were most widespread included high LDL-C (52.8%), high triglycerides (47.2%), and low HDL-C (42.6%). In dyslipidemic patients, complete healing of the ulcer was observed in 33.1% and 14.5% major amputation and death, respectively. On the contrary, patients without dyslipidemia showed better healing (62.5%), amputation (5.3%), and mortality (5.3%). Conclusion: Dyslipidemia is extremely common in diabetic foot and is linked to unhealing wounds, higher amputation rates, and mortality. The management and screening of lipids at an early age should be part of the diabetic foot care in Pakistan.